2013
DOI: 10.1002/ps.3620
|View full text |Cite
|
Sign up to set email alerts
|

Sea lice population and sex differences in P-glycoprotein expression and emamectin benzoate resistance on salmon farms in the Bay of Fundy, New Brunswick, Canada

Abstract: Sea lice bioassay and P-gp mRNA studies can be used to track EMB resistance and sex differences in EMB sensitivity and P-gp mRNA levels exist in the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 46 publications
3
56
1
Order By: Relevance
“…Also indicating a lack of costs, Atlantic Canada L. salmonis remained highly resistant over three generations without continued selection (Igboeli et al. ). Intermediate hybrid sensitivity suggests polygenic resistance (Espedal et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also indicating a lack of costs, Atlantic Canada L. salmonis remained highly resistant over three generations without continued selection (Igboeli et al. ). Intermediate hybrid sensitivity suggests polygenic resistance (Espedal et al.…”
Section: Introductionmentioning
confidence: 99%
“…) and reverse‐transcription quantitative PCR (RT‐qPCR) to profile gene expression responses of sensitive Pacific lice to EMB (0, 10, 25, 50 ppb) and to compare baseline and induced (0, 0.1, 25, 300, 1000 ppb) expression differences between sensitive and resistant Atlantic lice (Igboeli et al. ). Sex‐specific differences in EMB resistance have been identified (Westcott et al.…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of the ABC transporters was observed in populations of A. aegypti resistant to pyrethroids, thus marking these genes as potential indicators of a reduction in sensitivity to this type of chemical (Bariami et al, 2012). Of the ABC transporters, the Pglycoprotein (P-gp) has been related to the generation of resistance to EMB in L. salmonis, where an overregulation of this gene was present in resistant strains (Heumann et al, 2012;Igboeli et al, 2014). The present study showed an overregulation of P-gp in C. rogercresseyi treated with azamethiphos that was significantly greater than the response obtained in adults treated with deltamethrin, thus demonstrating a strong interaction of P-gp with organophosphates.…”
Section: Contigmentioning
confidence: 97%
“…Egg strings from L. salmonis were harvested from sea cage cultured Atlantic salmon (New Brunswick, Canada) from the BMA2A region (this region contains lice with elevated emamectin benzoate (EMB) resistance; Igboeli et al 2014) and were aerated in 13°C saltwater collected from the sea cage site and maintained at the Atlantic Animal Facility, Atlantic Veterinary College at 33-36 salinity through 10% daily water changes until nauplii hatched and molted to copepodids (∼6-8 d).…”
Section: Animalsmentioning
confidence: 99%